Search for ‘Self’ in Jamaica Kincaid’s Annie John, Lucy and See Now Then - Verma, Archana (Journal of English Language and Literature (ISSN: 2368-2132), 2018)
The subject of ‘self’ is a much wider concept which amalgamates the cultural issues and the social issues which eventually leads to the identity crisis of a black women. The study of Kincaid’s novels recapitulates the idea of the fight of an individual self right from the beginning till the end of life. The three novels run in continuation and present the different stages of a woman’s life and the struggle which she encounters at the every phase of life. This paper also contemplates the idea that a woman never fails to strive for her identity even in the adverse circumstances.